Competency Model for Product Owners and Product Managers - Barnett Urtecho, Sebastian J. (2023)
The objective of this article is to develop a competency model for Product Owners and Product Managers that enables them to perform successfully in their roles. The article goes through several stages, with the first being the study and analysis phase. In this stage, the problems, related work for the mentioned roles, and the literature used for the model design process will be analyzed. Subsequently, the competency model for Product Owners and Product Managers will be designed to establish the competencies that these roles should possess. This will also help companies in hiring qualified individuals for product development. Finally, the model will be validated through the evaluation of experts in the field, using virtual interviews and a Likert scale-based survey. These techniques will allow for the collection of quantitative data to support the validity of the model. © 2023 CISCI 2023 - Vigesima Segunda Conferencia Iberoamericana en Sistemas, Cibernetica e Informatica, Vigesimo Simposium Iberoamericano en Educacion, Cibernetica e Informatica, SIECI 2023